ANALYSIS OF REDUCTION 〖PM〗_(2.5) EMISSIONS WITH THE SHIFT FROM PRIVATE LOCAL TRANSPORTATION TO PEDESTRIAN AND BIKE SHARING IN CENTRAL JAKARTA CITY: M.H. THAMRIN AREA - Syafei, Arie Dipareza; Azizah, Naura Nensi; Nabila, Nasywa Ainun (Department of Environmental Engineering-Faculty of Civil, Planning, and Geo Engineering. Institut Teknologi Sepuluh Nopember, Surabaya, 2024)
Central Jakarta as one of the administrative cities in the DKI Jakarta Province has the highest populationdensity of 20,360 per km2. The number of motorized vehicles in Jakarta is recorded at 23,025,101 units. Thisfigure can be a crucial issue considering that the transportation sector is the largest contributor to airemissions with PM2.5 as the main pollutant. Jakarta's air quality is monitored as unhealthy (for sensitivegroups) with PM2.5 concentrations reaching two and a half times the safe limit according to WHO standards.This study aims to determine the percentage of interest of private vehicle users in the M.H Thamrin Area,Central Jakarta switch to pedestrians or bike. The result were then be used to calculate the emissions thatoccur reduction followed by the changes. The survey’s result were analyzed using the SPSS application todetermine significant factors related to the interest of private vehicle users to switch. Emission calculationsare carried out based on the Regulation of the Minister of Environment No. 12 in 2010. The result of thisstudy indicate that 91.5% of private vehicle users from 12,830 residents of the M.H. Thamrin area are willingto switch to pedestrians consisting of 65.1% motorcycle users and 34.9% car users. As many as 94.4% ofprivate vehicle users are willing to switch to bike sharing consisting of 63.2% motorcycle users and 36.8%car users. Several factors that significantly influence people's interest in switching are the availability of widepedestrian paths (> 2 m) and the low cost of using bike sharing (Rp3,000 - Rp7,000 per trip). With the effortto move private motor vehicles to pedestrians, PM2.5 emissions in the M.H. Thamrin Area, Central Jakartacan be reduced by 93.04%, which is equivalent to 0.656 tons of PM2.5/year. On the other hand the shifting ofprivate motor vehicles to bike sharing, will contribute to 92.87% of PM2.5 reduction, or 0.778 tons ofPM2.5/year